Theoretical study on longitudinal deformation of adjacent tunnel subjected to pre-dewatering based on Pasternak-Timoshenko beam model - Yang, Sun; Yao, Rong; Junping, Yu; Liqing, Zhu; Haibin, Ding; Lihong, Tong (Frontiers in Earth Science, 2023)
In this research, under the disturbance of pre-dewatering, the analytical solution of vertical displacement of the adjacent tunnel is derived using the two-stage analysis method. In the first stage, the effective stress principle was used to calculate the additional stress of the adjacent tunnel caused by dewatering. In the second stage, the Pasternak-Timoshenko beam model was used to simulate the interaction between the tunnel and soil, taking the tunnel shear deformation into account. By referring to the calculation results of existing literature, the correctness of the proposed method is verified, and the influencing factors of the longitudinal displacement of the tunnel are further analyzed. The results show that the deformation of the existing tunnel increases with the permeability coefficient. The decrease of the tunnel shear modulus can lead to the rapid increase of the tunnel's vertical displacement, so the shear stiffness should be considered in the analysis of its deformation. The increase in dropping amplitude of the water level in the well will decrease the water level in the surrounding strata. According to the different relative positions of the tunnel and the water table, there are two forms of additional load on the tunnel. Before the water level drops to the tunnel axis, the tunnel's Additional load and displacement gradually increase.